Anti-Inflamm-Ageing and/or Anti-Age-Related Disease Emerging Treatments: A Historical Alchemy or Revolutionary Effective Procedures? - Carmela Rita Balistreri (Mediators of Inflammation)
The “long-life elixir” has long represented for humans a dream, a vanity’s sin for remaining young and to long survive. Today, because of ageing population phenomenon, the research of antiageing interventions appears to be more important than ever, for preserving health in old age and retarding/or delaying the onset of age-related diseases. A hope is given by experimental data, which evidence the possibility of retarding ageing in animal models. In addition, it has been also demonstrated in animal life-extending studies not only the possibility of increasing longevity but also the ability to retard the onset of age-related diseases. Interestingly, this recent evidence is leading to promise of obtaining the same effects in humans and resulting in benefits for their health in old ages. In order to achieve this goal, different approaches have been used ranging from pharmacological targeting of ageing, basic biological assays, and big data analysis to the recent use of young blood, stem cells, cellular, genetic, and epigenetic reprogramming, or other techniques of regenerative medicine. However, only a little fraction of these approaches has the features for being tested in clinical applications. Here, new emerging molecules, drugs, and procedures will be described, by evidencing potential benefits and limitations.